Skrining Virtual dan Elusidasi Moda Ikatan Senyawa dalam Bawang Putih (Allium Sativum L.) sebagai Penghambat Reseptor Advanced Glycation end Products - Esti Mulatsari; Esti Mumpuni; Ikhsan Ramadhan (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Diabetic has long-term effects such as atherosclerosis, nephropathy, and retinopathy caused by the formation of Advanced Glycation End Products (AGEs). In vitro studies on garlic extract (Allium sativum L.) have been carried out on the inhibition activity of AGEs formation, but inhibitory mechanisms and which active compounds are involved in these activities are unknown. This study aims to do a virtual screening of garlic compounds (Allium sativum L.) on Advanced Glycation Endproduct receptors so that active compounds can be considered as candidates for drug compounds. The method used is molecular docking with PLANTS, YASARA, MarvinSketch software, and visualization of test compound bonds on receptor amino acids using PyMOL. Pyridoxamine and Aminoguanidine as a positive control of AGEs inhibitors. The docking results of 24 test compounds obtained seven compounds that active in inhibiting 3B75 receptor and five compounds in 3O3U receptor. Candidates for drug compounds consist of organosulfur, phenols and flavonoids. Ɣ-glutamyl-cysteine, E-ajoene, Nα- (1-Deoxy-Dfructose-1-YL) -L-Arginine, Kaempferol-3-o-β-D-glucopyranose, and Iso-rhamnetin-3-o-β -D-glucopyranose are compounds in garlic which have an ability to inhibit 3B75 and 3O3U receptors and predicted have better activity than pyridoxamine and aminoguanidine.